2003
DOI: 10.1098/rspb.2003.2359
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of soil-burrowing cockroaches (Blattaria: Blaberidae) from wood-burrowing ancestors following an invasion of the latter from Asia into Australia

Abstract: Morphologically similar cockroaches in the subfamilies Panesthiinae and Geoscapheinae (Blattaria: Blaberidae) display contrasting feeding habits, behaviour and biogeographical distributions. Panesthiinae, found throughout Asia and Australia, all live in and feed on decaying wood that they burrow into. Geoscapheinae are restricted to Australia and construct and live in burrows in the soil, where they feed on dry leaves taken from the surface. A lack of knowledge about phylogenetic relationships among these cock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 36 publications
4
44
1
Order By: Relevance
“…These unsurprising results have been suggested several times and concern the monophyly of Blaberidae, (Geoscapheinae + Panesthiinae) and Oxyhaloinae (Maekawa et al 2003;Inward 2007;Pellens et al 2007;Djernaes et al 2012;Legendre et al 2014Legendre et al , 2015. Likewise, a strong support was found, here and in previous studies, for Gyninae, Panchlorinae and Pycnoscelinae.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These unsurprising results have been suggested several times and concern the monophyly of Blaberidae, (Geoscapheinae + Panesthiinae) and Oxyhaloinae (Maekawa et al 2003;Inward 2007;Pellens et al 2007;Djernaes et al 2012;Legendre et al 2014Legendre et al , 2015. Likewise, a strong support was found, here and in previous studies, for Gyninae, Panchlorinae and Pycnoscelinae.…”
Section: Discussionsupporting
confidence: 87%
“…Later, cockroach systematists identified several morphological synapomorphies supporting the monophyly of Blaberidae (Grandcolas 1996;Klass & Meier 2006; brood sac underneath the female genitalia, sclerite R3v small, first vein of vannus with many basal rami, tracheation very dense and tracheae vesicle-shaped, presence of a muscle connecting sclerite L2 and pouch lve). Monophyly has also repeatedly been found with molecular data as well (Maekawa et al 2003;Inward 2007;Pellens et al 2007;Djernaes et al 2012;Legendre et al 2014Legendre et al , 2015.…”
Section: Introductionmentioning
confidence: 54%
“…Our results support the hypothesis that the Australian taxa in Panesthiinae and Geoscapheinae are descendants of Asian wood feeders that invaded Australia via Wallace's Line [19]. First, Australian lineages are nested among Asian lineages in the tree (figure 2 evidence, which is almost certainly unattainable.…”
Section: (B) Biogeography Of Panesthiinae and Geoscapheinaesupporting
confidence: 82%
“…A molecular phylogenetic study of a limited number of taxa from Panesthiinae and Geoscapheinae (17 and 4, respectively) showed that the former evolved in Asia, later colonizing Australia and giving rise to Geoscapheinae [19]. The four species of Geoscapheinae examined formed a monophyletic group that was relatively distant from the two Australian species of Panesthiinae included in the study [19].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation